2017
DOI: 10.5935/0004-2749.20170043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hemodialysis on corneal and anterior chamber morphometry and intraocular pressure in patients with end-stage renal disease

Abstract: Uncorrected IOP, corrected IOP, CCT, and CV values decreased after HD, whereas the anterior chamber morphometry values remained similar between the measurements performed before and after HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 0 publications
1
15
1
6
Order By: Relevance
“…Ocular abnormalities are frequently associated with patients on chronic dialysis, including IOP fluctuation, corneal calcification, retinal hemorrhage, retinal toxicity related to desferrioxamine, anterior ischemic neuropathy, and uremic optic neuropathy [ 24 ]. Among them, the relationship between IOP changes and dialysis has been reported with various results [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 25 ]. Moreover, there has long been a debate regarding whether transient IOP changes during HD would result in the progression of glaucoma [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular abnormalities are frequently associated with patients on chronic dialysis, including IOP fluctuation, corneal calcification, retinal hemorrhage, retinal toxicity related to desferrioxamine, anterior ischemic neuropathy, and uremic optic neuropathy [ 24 ]. Among them, the relationship between IOP changes and dialysis has been reported with various results [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 25 ]. Moreover, there has long been a debate regarding whether transient IOP changes during HD would result in the progression of glaucoma [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have discussed intraocular pressure (IOP) changes during HD since the first demonstration of an increase in IOP during dialysis in 1964 [ 5 , 6 ]. Some studies have revealed that IOP may be elevated [ 6 , 7 , 8 , 9 , 10 ], some have shown that IOP does not change [ 11 , 12 ], and some have demonstrated that IOP decreases [ 13 , 14 , 15 , 16 , 17 ]. However, these previous results were either limited by small patient numbers, a short follow-up period, or lack of a comparative group.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although hemodialysis is the main treatment of end-stage renal failure (ESRD), acute and chronic complications may occur after this treatment. 4 Hypovolemia and increased osmotic pressure after hemodialysis may affect eye tissues with large amounts of blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…During chronic hemodialysis (HD), ocular complications such as significant IOP increments, glaucoma, and retro‐ocular pain have been reported in several case studies . Considering that patients treated with chronic HD experience important changes in blood pressure and body fluids volume and composition , several studies have evaluated a potential association between changes in IOP during HD . IOP increments are linked to the incidence of symptoms such as blurred vision, decreased visual acuity, and headache during HD sessions .…”
mentioning
confidence: 99%
“…Several studies of IOP and HD have measured IOP only before HD and after HD, or included one intermediate measure , with contradictory results: some indicate that IOP increases , while others reported a decrease of IOP after HD or no change . The most recent studies showed a decrease of IOP after HD , while other studies report increases during the second HD hour but no change after HD . Additionally, IOP changes have been evaluated during hemofiltration (16) but there are no studies regarding IOP changes during hemodiafiltration (HDF).…”
mentioning
confidence: 99%